Risk Score for the Prediction of Contrast-Induced Nephropathy in Elderly Patients Undergoing Percutaneous Coronary Intervention. (April 2013) - Fu, Naikuan; Li, Ximing; Yang, Shicheng; Chen, Yongli; Li, Qiong; Jin, Dongxia; Cong, Hongliang
We developed a risk score for contrast-induced nephropathy (CIN) in elderly patients (n = 668) before percutaneous coronary intervention (PCI). Another 277 elderly patients were studied for validation. Based on the odds ratio, risk factors were assigned a weighted integer; the sum of the integers was the risk score. Among the 668 elderly patients, 105 (15.7%) experienced CIN. There were 9 risk factors for CIN (with weighted integer): estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 (4), diabetes (3), left ventricular ejection fraction <45% (3), hypotension (2), age >70 years (2), myocardial infarction (2), emergency PCI (2), anemia (2), and contrast agent volume >200 mL (2). The incidence of CIN was 3.4%, 11.9%, 36.9%, and 69.8% in the low-risk (≤4), moderate risk (5-8), high-risk (9-12), and very-high-risk groups (≥13). The model demonstrated good discriminative power in the validation population ( c statistic = 0.79). This score can be used to plan preventative measures.